The walking Quran : Islamic education, embodied knowledge, and hi story in West Africa - Ware, Rudolph T. (Chapel Hill, North Carolina : The University of North Carolina Pr ess, 2014)
"Typesetter: code used below Spanning a thousand years of history- -and bringing the story to the present through ethnographic fieldwork i n Senegal, Gambia, and Mauritania--Rudolph Ware documents the profound significance of Quran schools for West African Muslim communities. Such schools peacefully brought Islam to much of the region, becoming strik ing symbols of Muslim identity. Ware shows how in Senegambia the school s became powerful channels for African resistance during the eras of th e slave trade and colonization. While illuminating the past, Ware also makes signal contributions to understanding contemporary Islam by demon strating how the schools' epistemology of embodiment gives expression t o classical Islamic frameworks of learning and knowledge. Today, many Muslims and non-Muslims find West African methods of Quran schooling pu zzling and controversial. In fascinating detail, Ware introduces these practices from the viewpoint of the practitioners, explicating their em phasis on educating the whole human being as if to remake it as a livin g replica of the Quran. From this perspective, the transference of know ledge in core texts and rituals is literally embodied in people, helpin g shape them--like the Prophet of Islam--into vital bearers of the word of God. "--
"Spanning a thousand years of history--and bringing the story to the present through ethnographic fieldwork in Senegal, Gambia, and Maurita nia--Ware documents the profound significance of Quran schools for West African Muslim communities. Such schools peacefully brought Islam to m uch of the region, becoming striking symbols of Muslim identity. Ware s hows how in Senegambia the schools became powerful channels for African resistance during the eras of the slave trade and colonization. While illuminating the past, Ware also makes signal contributions to understa nding contemporary Islam by demonstrating how the schools' epistemology of embodiment gives expression to classical Islamic frameworks of lear ning and knowledge"--
Includes bibliographical references (p. 295-317) and index.
Keywords: Quran -- Study and teaching -- Africa, West; Islamic religious education -- Africa, West